PENINGKATAN KETERAMPILAN BERBICARA MELALUI MODEL COOPERATIVE LEARNING TIPE EXAMPLE NON EXAMPLE PADA MURID KELAS IV SDN 20 PIAI KOTA PADANG - Wilda, Fitria; Adrias; Desyandri; Elfia Sukma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low speaking skills of fourth-grade students at SDN 20 Piai, Padang City. The problems were indicated by: (1) students still feeling hesitant and shy when asked to speak about the material explained by the teacher; (2) when speaking, students often seemed to run out of words, resulting in frequent pauses to recall what they intended to say; (3) students’ vocabulary mastery was still relatively low, which impacted their difficulty in constructing sentences and expressing ideas orally; and (4) students were not yet accustomed to speaking actively during the learning process. The purpose of this study was to describe the improvement of students’ speaking skills through the use of the cooperative learning model of the Example Non Example type in the fourth grade of SDN 20 Piai, Padang City. This research was a Classroom Action Research (CAR) employing both quantitative and qualitative approaches. The subjects of this study were the teacher and 27 fourth-grade students of SDN 20 Piai. The results of the study showed an improvement in students’ speaking skills. The average speaking skill score increased from 72.04 with a mastery percentage of 33.33% in Cycle I Meeting 1 to 77.96 with a mastery percentage of 55.55% in Cycle I Meeting 2, and further increased to 84.07 with a mastery percentage of 85.28% in Cycle II. Therefore, it can be concluded that the cooperative learning model of the Example Non Example type is effective in improving the speaking skills of fourth-grade students at SDN 20 Piai, Padang City.